A redescription of Trachelosaurus fischeri from the Buntsandstein (Middle Triassic) of Bernburg, Germany: the first European Dinocephalosaurus-like marine reptile and its systematic implications for long-necked early archosauromorphs - Stephan N. F. Spiekman; Martín D. Ezcurra; Adam Rytel; Wei Wang; Eudald Mujal; Michael Buchwitz; Rainer R. Schoch (Swiss Journal of Palaeontology, 2024)
Abstract Some of the earliest members of the archosaur-lineage (i.e., non-archosauriform archosauromorphs) are characterised by an extremely elongated neck. Recent fossil discoveries from the Guanling Formation (Middle Triassic) of southern China have revealed a dramatic increase in the known ecomorphological diversity of these extremely long-necked archosauromorphs, including the fully marine and viviparous Dinocephalosaurus orientalis. These recent discoveries merit a reinvestigation of enigmatic Triassic diapsid fossils from contemporaneous European deposits housed in historical collections. Here, we provide a redescription of Trachelosaurus fischeri, represented by a single, disarticulated specimen first described in 1918. Due to its unique morphology, which includes short, bifurcating cervical ribs, and a high presacral vertebral count, this taxon has been referred to either as a “protorosaurian” archosauromorph or a sauropterygian. Our revision clearly shows that Trachelosaurus represents the first unambiguous Dinocephalosaurus-like archosauromorph known from outside the Guanling Formation. Our finding has important systematic implications. Trachelosauridae Abel, 1919 represents the senior synonym for the recently identified Dinocephalosauridae Spiekman, Fraser and Scheyer, 2021. Based on our phylogenetic analyses, which employ two extensive datasets, we also corroborate previous findings that tanystropheids and trachelosaurids represent two families within a larger monophyletic group among non-crocopodan archosauromorphs, which is here named Tanysauria (clade nov.). Trachelosauridae is minimally composed of Trachelosaurus fischeri, Dinocephalosaurus orientalis, Pectodens zhenyuensis, and Austronaga minuta, but one of our analyses also found a probably taxonomically broader clade that may also include Gracilicollum latens and Fuyuansaurus acutirostris. Trachelosaurus fischeri considerably expands the known spatial and temporal range of Trachelosauridae to the earliest Anisian and the Central European Basin. Our findings add to the growing evidence for the presence of a diverse group of fully marine reptiles during the Middle Triassic among Tanysauria. These trachelosaurids possess flipper-like limbs, high vertebral counts, and elongate necks, thus superficially resembling long-necked Jurassic and Cretaceous plesiosaurs in some regards.